A Avaliação Nacional da Alfabetização (ANA) na concepção de diferentes sujeitos da cidade de Rio Verde-GO (2014-2016) - Ataides, Fernanda Barros (2019)
This study had as a main goal to analyze the conception that students, families, teachers, pedagogical supervisors, managers and school secretaries have regarding the National Assessment of Alphabetization (ANA). ANA is one of the most recent evaluations that compound the National System Evaluation of Basic Education − Saeb. It was documented in 2013, by ordinance nº 867, of July 4, 2012, recommending that all children must be literate until eight years of age. However, we questioned whether the ANA itself is capable of making improvements in education, since the conception that has guided this evaluation practice after all starts from a limited, conflicting, capitalist logic, with mere meritocratic, selective and classificatory principles, aimed at attending to the job market and not the school needs. As for methodological procedures, we chose to conduct research based on a qualitative approach; we materialized the study through questionnaires and interviews, involving subjects of the municipal teaching network of Rio Verde-GO. The research had also a bibliographical review and documentary analysis. The development of the study allowed us to conclude that most of the research participants reproduce the principle of the State which sees ANA as an indicator of quality. We also noticed that there is an external-versus-internal tension, whereas ANA holds an indicator focused on students' performance regardless of the school floor; On the other hand, we have this internal tension that comes across, with its needs and difficulties that ANA cannot express. In that sense, the percentage of people who perceive ANA as an assessment of learning is high, and that could be. In Brazil, however, the goal and intention of this evaluation is otherwise: it tries to collect good results; it strengthens the idea of curricular narrowing, centering the teaching in Portuguese language and mathematics, it privileges the merit and naturalizes the excluding logic.We must break with this evaluation practice, in defense of an external evaluation, based on formative principles, as we believe that ANA, in dialogue with an assessment of learning, can bring important information that favors the planning and rethinking of actions within the school.